An interpretive review of consensus statements on clinical guideline development and their application in the field of traditional and complementary medicine. Issue 1 (December 2017) - Hunter, Jennifer; Leach, Matthew; Braun, Lesley; Bensoussan, Alan
Abstract Background Despite ongoing consumer demand and an emerging scientific evidence-base for traditional and complementary medicine (T&CM), there remains a paucity of reliable information in standard clinical guidelines about their use. Often T&CM interventions are not mentioned, or the recommendations arising from these guidelines are unhelpful to end-users (i.e. patients, practitioners and policy makers). Insufficient evidence of efficacy may be a contributing factor; however, often informative recommendations could still be made by drawing on relevant information from other avenues. In light of this, the aim of this research was to review national and internationally endorsed consensus statements for clinical guideline developers, and to interpret how to apply these methods when making recommendations regarding the use of T&CM. Method The critical interpretive review method was used to identify and appraise relevant consensus statements published between 1995 and 2015. The statements were identified using a purposive sampling technique until data saturation was reached. The most recent edition of a statement was included in the analysis. The content, scope and themes of the statements were compared and interpreted within the context of the T&CM setting; including history, regulation, use, emerging scientific evidence-base and existing guidelines. Results Eight consensus statements were included in the interpretive review. Searching stopped at this stage as no new major themes were identified. The five themes relevant to the challenges of developing T&CM guidelines were: (1) framing the question; (2) the limitations of using an evidence hierarchy; (3) strategies for dealing with insufficient, high quality evidence; (4) the importance of qualifying a recommendation; and (5) the need for structured consensus development. Conclusion Evidence regarding safety, efficacy and cost effectiveness are not the only information required to make recommendations for clinical guidelines. Modifying factors such as burden of disease, magnitude of effect, current use, demand, equity and ease of integration should also be considered. Uptake of the recommendations arising from this review are expected to result in the development of higher quality clinical guidelines that offer greater assistance to those seeking answers about the appropriate use of T&CM.